Influence of fault forms on the evolution of concrete damage patterns in tunnels - Chen, Yuting; Wu, Jie; Zhang, Shuai; Teng, Shuai (Frontiers in Materials, 2022)
Estimating quickly and accurately the seismic weak surface of fault tunnel is one of the severe challenges in tunnel seismic design. Therefore, the strong nonlinear response of the Jinping-II Hydropower Station under the dislocations of positive, reverse, and slip faults was investigated through the finite element method using a static elastoplastic model. The results reveal the damage and failure mechanism of tunnels under different faults. By using IDA damage rating index, the damage initiation, evolution and development process of tunnels under different types of faults are analyzed. The results showed that the effected area of fault dislocation is concentrated and intense, which is mainly distributed along the two sides of the fault surface. The damage of the positive and reverse faults to the tunnel extends from the arch waist to the vault and the invert of the arch, while the influence of the slip fault on the tunnel is the greatest at the vault and invert of the arch, and then extends to the arch waist. In terms of the impact range, the reverse fault is the biggest, followed by the slip fault, while the positive fault is the lowest. This study contributes to the design and construction of tunnels through the faults.